Pembaharuan Islam Muhammad Ibn Abdul Wahhab di Mesir - Solekha, Amalia (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
A change that occurs in the life of Muslims in the millennial period today is sometimesnot in accordance with the efforts of renewal of the thoughts of the reformers among theprevious Islamic community. In the 18 M, a renewal movement in Egypt was born whichwas spearheaded by one of the leaders of reformation namely Muhammad Ibn AbdulWahhab from Saudi Arabia. The background of the renewal movement by Muhammad IbnAbdul Wahhab was due to a setback in the Muslim Community. Writing is an exposition tofind out how renewal is carried out by the figure of reformer Muhammad Ibn AbdulWahhab.